Korelasi Kualitas Tidur Buruk dengan Penurunan Fungsi Kognitif pada Lansia Panti Sosial Tresna Werdha Wana Seraya Denpasar - Wildan Sifa’ul Mahsyar; I Made Oka Adnyana; Desak Ketut Indrasari Utami; Ida Ayu Sri Wijayanti (Pusat Riset dan Inovasi Nasional, 2026)
Background: The increasing elderly population brings health challenges in the form of sleep disorders and cognitive decline. Poor sleep quality is often associated with decreased cognitive performance, but previous studies have shown inconsistent results. Objective: This study aims to determine the correlation between poor sleep quality and cognitive decline in the elderly at the Wana Seraya Social Home for the Elderly, Denpasar. Method: This study is an analytical observational study with a cross-sectional design conducted from November 2025 to January 2026. The research instrument used the Pittsburgh Sleep Quality Index to assess sleep quality and the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina) to assess cognitive function. Data were analyzed using the Spearman Rank correlation test. Results: The majority of respondents had poor sleep quality (69.7%) and impaired cognitive function (97%). The results of statistical analysis showed a weak positive correlation (r = 0.268) but the relationship was not statistically significant (p = 0.131). Conclusion: There was no significant relationship between poor sleep quality and cognitive decline in the elderly at the study site. These results indicate that sleep quality is not the sole factor contributing to the decline in cognitive function in the elderly.